STUDI PENGEMBANGAN EKOWISATA BAHARI DI PULAU PASIR PUTIH KABUPATEN POLEWALI MANDAR - Pasak, Hans Agung; Manapa, Esther Sanda; Ukkas, Marzuki (Jurnal Ilmu Kelautan SPERMONDE, 2017)
In 2011, the government of West Sulawesi has planned on sea conservation area covering the islands in Mandar Bay of PolewaliMandar Regency. One of the islands that has been declared as sea conservation area is the Pasir Putih Island. In order todevelop maritime echotourism in the Pasir Putih Island than a research has been carry out starting in July to December 2015.The purposes of this research are: (1) to evaluate the suitability of coral and the species association for diving activity, (2) toevaluate suitability of the area for snorkeling, (3) to estimate the carrying capacity of the area for echotourism activity. Theresult of this research indicates that the coral area for the diving activity in Pasir Putih Island is categorized as on conditionalof appropriate. The carrying capacity of the area was estimated to 45 person per day for diving activity, while for snorkelingtour the area is quite appropriate for 90 person per day. To support marine ecotourism development, the following strategies areneeded: (1). Establishing cooperation with local government in maintaining the local wisdom. (2) Estabilishing core zone asRegional Marine Conservation Area (KKLD), (3). Publishing guidebooks for the ecotourism.Keywords: Marine ecotourism, Pulau Pasir Putih, Polewali Mandar, suitability for diving, suitability for snorkeling, carrying